Characterization of the Genes for Two Protocatechuate 3,4-Dioxygenases from the 4-Sulfocatechol-Degrading Bacterium Agrobacterium radiobacter Strain S2 - Contzen, Matthias (American Society for Microbiology, 2000)
The genes for two different protocatechuate 3,4-dioxygenases (P34Os) were cloned from the 4-sulfocatechol-degrading bacterium Agrobacterium radiobacter strain S2 (DSMZ 5681). The pcaH1G1 genes encoded a P34O (P34O-I) which oxidized protocatechuate but not 4-sulfocatechol. These genes were part of a protocatechuate-degradative operon which strongly resembled the isofunctional operon from the protocatechuate-degrading strain Agrobacterium tumefaciens A348 described previously by D. Parke (FEMS Microbiol. Lett. 146:3–12, 1997). The second P34O (P34O-II), encoded by the pcaH2G2 genes, was functionally expressed and shown to convert protocatechuate and 4-sulfocatechol. A comparison of the deduced amino acid sequences of PcaH-I and PcaH-II, and of PcaG-I and PcaG-II, with each other and with the corresponding sequences from the P34Os, from other bacterial genera suggested that the genes for the P34O-II were obtained by strain S2 by lateral gene transfer. The genes encoding the P34O-II were found in a putative operon together with two genes which, according to sequence alignments, encoded transport proteins. Further downstream from this putative operon, two open reading frames which code for a putative regulator protein of the IclR family and a putative 3-carboxymuconate cycloisomerase were identified.